2012
DOI: 10.1167/iovs.11-9325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Contrast, Stimulus Density, and Viewing Distance on Multifocal Steady-State Visual Evoked Potentials (MSVs)

Abstract: The response per unit area indicated that cortical folding diminishes responses to larger stimuli. Viewing distance did not greatly affect response amplitude. This suggested that we can use similar, but scaled, stimuli to study central and peripheral disease. The rapidly saturating contrast responses imply that there would be nothing lost from testing at contrasts as low as 20% given that higher, saturating contrasts might mask visual field defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
4
15
0
Order By: Relevance
“…The M100 responses showed substantial modulations based on the contrast of the image (see Figure 2) and did not change based on image noise or cognitive task. In accordance with previous electrophysiological studies (Abdullah et al 2012;Gebodh, Vanegas, and Kelly 2017;Maddess, James, and Bowman 2005), high contrast stimuli elicited larger and faster M100 responses as compared to low contrast stimuli (p<.001).…”
Section: Meg Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The M100 responses showed substantial modulations based on the contrast of the image (see Figure 2) and did not change based on image noise or cognitive task. In accordance with previous electrophysiological studies (Abdullah et al 2012;Gebodh, Vanegas, and Kelly 2017;Maddess, James, and Bowman 2005), high contrast stimuli elicited larger and faster M100 responses as compared to low contrast stimuli (p<.001).…”
Section: Meg Resultssupporting
confidence: 92%
“…The M100 responses showed substantial modulations based on the contrast of the image (see Figure 2) and did not change based on image noise or cognitive task. In accordance with previous electrophysiological studies (Abdullah et al 2012;Gebodh, Vanegas, and Similar FA correlations were found with the other M100 electrophysiological properties (amplitude: r=+0.29, p=0.04, robust r=+0.35, p=0.02; power: r=+0.34, p=0.02, robust r=+0.34, p=0.02; inter-trial coherence: r=+0.29, p=0.04, robust r=+0.29, p=0.04).…”
Section: Meg Resultssupporting
confidence: 91%
“…However, in the midfrequency range, the recordings were sufficiently short for clinical application (e.g., 91.5 seconds at 12 Hz). This is close to the resolution presented earlier 5,31…”
Section: Discussionsupporting
confidence: 90%
“…So far, quadrant recordings with pattern-reversal stimulation were made with separate stimulation of each field quadrant 20–22. More recently, Maddess and colleagues23 demonstrated the value of the incommensurate frequency technique for grating stimulation on a monitor with several discrete reversal frequencies. In the present study, we show that LEDs can be used in arrays that can deliver pattern-reversal stimuli with very small temporal frequency differences.…”
Section: Discussionmentioning
confidence: 99%
“…Since the use of multiple simultaneous inputs reduces the time needed for assessments (e.g., example of clinical visual field assessment) (Abdullah, Aldahlawi, Rosli, Boon, & Maddess, 2012), frequency-tagging EEG can be a very fast and efficient measure. Given the short recording time of the frequency-tagging paradigm and the robustness of the obtained results, the method could be used as a fast marker of social preference, which may ultimately be incorporated in the clinical diagnostic procedure.…”
Section: Discussionmentioning
confidence: 99%